Integration of Photovoltaic Generation Within a Modeling Framework for Energy Hubs - Ramos-Teodoro, Jerónimo; Rodríguez, Francisco; Berenguel, Manuel (Frontiers in Control Engineering, 2022)
Energy efficiency is a topic that counts with many publications related to resources exploitation at a local scale, since via a well-performed energy management, substantial environmental and economic benefits can be achieved. In this article, the models used to forecast the photovoltaic power yield in two distinct facilities are described. These facilities are part of the same production plant, which makes use of different heterogeneous resources (carbon dioxide, water, thermal energy and electricity) and has already been analyzed in a problem that consists in finding the set of variables that minimizes the operation cost. In order to predict the power production for both photovoltaic fields, the expressions for radiation on sloped surfaces and the equivalent circuit for solar cells are employed, and the inverters and wire-transmission loss effects are considered. Furthermore, their integration within a general-purpose modeling framework for energy hubs is demonstrated. The comparison between validation results and production real data show that in spite of the slight overestimation of the energy yield, the models are suitable to forecast both facilities production with a suitable accuracy, as the R2 coefficients of both facilities lie between 0.95 and 0.96.